2010
DOI: 10.1200/jco.2009.25.9366
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Human Epidermal Growth Factor Receptor 2 Immunohistochemistry in Breast Core Needle Biopsies

Abstract: IHC 3+ scores on CNBs proved to be reliable in four of the five participating institutions if scoring followed the ASCO-CAP criteria. Therefore, accurate determination of HER2 status in breast cancer is possible on CNB using the common strategy to screen all cases by IHC and retest only 2+ scores by FISH. Prerequisites are quality assurance and the application of the new ASCO-CAP criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 43 publications
1
41
0
1
Order By: Relevance
“…28,31,32 Middleton et al 33 demonstrated that adherence to the ASCO/CAP guidelines resulted in greater IHC-FISH concordance, although the improvement was only 0.5%. Our data showed a significant improvement in concordance rates after implementation of the guidelines.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…28,31,32 Middleton et al 33 demonstrated that adherence to the ASCO/CAP guidelines resulted in greater IHC-FISH concordance, although the improvement was only 0.5%. Our data showed a significant improvement in concordance rates after implementation of the guidelines.…”
Section: Commentmentioning
confidence: 99%
“…Crushed tumor cells and nonspecific staining at the edges are frequently seen in small biopsy specimens. 27,32 These artifacts may result in higher reading by the machine. Based on our experience, scoring of small biopsy specimens is more problematic than for excision specimens, because of limited tissue and overlapping fields.…”
Section: Commentmentioning
confidence: 99%
“…However, the application of ASCO/CAP guidelines as well as proficiency tests have improved the accuracy of HER2 determination in the last few years [34].…”
Section: Pathological Complete Response (Pcr) Following Neoadjuvant Cmentioning
confidence: 99%
“…Reliable, high-quality HER2 testing for clinical use is of paramount importance for the correct identification of patients who would benefit from HER2-targeted therapies. 1,[14][15][16][17][18] False-negative HER2 assessments could result in denial of an effective treatment, while false-positive assessments may lead to inappropriate administration of a potentially harmful, costly, and ineffective HER2-targeted therapy, or exclusion from treatment with other targeted therapies in the HER2-negative setting. 1,8,11,19,20 Despite 410 years of routine HER2 testing, studies have demonstrated variability in HER2 positivity assessments between local pathology laboratories and central testing centers, posing a challenge for clinicians.…”
mentioning
confidence: 99%